Elaboração e caracterização fisico-química de dieta enteral artesanal contendo alimentos convencionais do municipio de Coari, estado do Amazonas, Brasil - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
INTRODUCTION: The administration of enteral diet is a well accepted therapy in patients who do not fully reach their nutritional needs and has contributed to reducing mortality and morbidity. Despite all the benefits and privileges of using this therapy, its use is restricted due to the high cost of industrialized diets. The alternative to this problem are the handmade diets consisting of formulas prepared with fresh food plus other dietary sources of carbohydrates and protein, and mineral supplements. However, the chemical composition of these diets handmade enteral create doubts in their employability because of the emergence of uncertainties about the nutritional quality of these formulas .OBJECTIVES: This study aimed to develop a handmade enteral diet with defined chemical composition and low cost using conventional foods in the municipality of Coari, Amazonas State, Brazil. MATERIALS AND METHODS: We used the arowana (Osteoglonum bicirrhosum), cassava (Manihot esculenta Crantz), the peach palm (Bactris gasipaes), and pigweed (Amaranthus deflexus L.). These were processed in order to obtain flour and protein concentrate and then used in the preparation of a formula, calculating proportions of each food corresponding to the composition of the recommendation for enteral nutrition. Then settled dilution in the ratio 100 g diet for 150 ml of water and were carried out analyzes of stability, fluidity, gravity drip, chemical composition, mineral content, aminoacidic profile, fatty acid profile, counts molds and yeasts, total counts of mesophilic, Salmonella sp. and financial viability. RESULTS: The formula presented protein value of 13.18 g / 100 g 1.99 g / 100 g of lipids, 3,64 g / 100 g of ashes, 73.03 g / 100 g and 5.16 g carbohydrate / 100 g of fiber. With respect to mineral content, were found 52.48 mg / g 100 Sodium, 24.32 mg / 100 g of calcium 64.04 mg / 100 g of magnesium, 1.46 mg / 100g manganese, 5 95 mg / 100 g Zinc, 2.22 mg / 100 g of copper and 0.46 mg / 100 g of iron. With dilution 1 g: 1.5 ml water, diet showed caloric density of 1.55 kcal / ml and adequate fluidity to gravitational administration, drip with an average of 68 drops per minute. Obtained a formula the right balance between saturated fatty acids, monounsaturated and polyunsaturated. It was observed significant levels of polyunsaturated fatty acids, relevant to the maintenance and improvement of health (ω-3 fatty acids and ω-6), and essential amino acid content above the recommended. The formulated showed microbiological standards appropriate to the current legislation and apparent cost of R$ 0.56 CONCLUSION: handmade diet showed adequate fluidity, easy preparation and low cost, being characterized as a specialized diet because of the nutritional composition, which can be classified as high calorie, normal protein, high-carbohydrate, hypolipidic and fibers. The results also indicated that the prepared formulated has high quality protein and lipid for enteral nutrition, may be characterized as immunomodulatory formulas.
Keywords: Nutrição Enteral; Dieta Artesanal; Alimentos Amazônicos; Enteral Nutrition; Craft diet; Amazon foods; CIÊNCIAS AGRÁRIAS: CIÊNCIA E TECNOLOGIA DE ALIMENTOS: CIÊNCIA DE ALIMENTOS